2015
DOI: 10.15171/jlms.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Surface Treatment Methods and MDP Monomer on Resin Cementation of Zirconia Ceramics an In Vitro Study

Abstract: Tribochemical silica coating is an effective method for achieving an acceptable bond between zirconia and resin cement. Use of a MDP monomer containing resin cement increases the bond strength of sandblasted zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
“…A range of techniques is available for conditioning ceramic surfaces to enhance adhesion. Bond strength can also be influenced by parameters other than surface conditioning such as the application of silane [ 8 ], the composition of the ceramic material [ 9 ], or the nature and composition of resin cements and composites [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 However, cementation of oxide ceramic restorations with resin-based materials can improve their marginal adaptation. 10 The application of 10-methacryloyloxydecyl dihydrogen phosphate (MDP)-containing bonding agents can increase bond strength to zirconia [13][14][15][16][17][18] because of an interaction between the hydroxyl groups of MDP and the cationic surface of zirconia. 19,20 Establishing a microretentive structure on zirconia is difficult because zirconia, with its high crystalline content without any silica phase, is resistant to hydrofluoric acid etching.…”
mentioning
confidence: 99%